Upaya Guru Pendidikan Agama Hindu Dalam Meningkatkan Motivasi Belajar Siswa Hindu Di SMP Negeri 3 Dusun Selatan - Rena Patmawati; Mitro Mitro; I Gede Dharman Gunawan (Tampung Penyang, 2023)
Teacher effort is the effort made by teachers as professional educators in educating, guiding, directing and evaluating students by developing all their potential. Self-motivation to continue learning is very important for every Hindu student, because this motivation will inspire students to continue learning. On the other hand, without motivation, students will find it difficult to understand the material that has been explained by the teacher. Because motivation is able to build and change a person's behavior after getting motivation from other people, because motivation is very important for Hindu students. This article examines the efforts of Hindu religious education teachers in increasing the learning motivation of Hindu students at SMP Negeri 3 Dusun Selatan. The method used was a qualitative approach and purposive sampling technique to determine informants. The data analysis technique is carried out through four stages, namely: data collection, data reduction, data presentation, and drawing conclusions. The results of this research show that the efforts of Hindu religious education teachers to increase the learning motivation of Hindu students at SMP Negeri 3 Dusun Selatan in the learning process in the classroom with a series of planning and preparation including methods, media and teaching materials in accordance with the 2013 curriculum book. The learning process includes preliminary activities, core, and cover. The form of motivation given in the form of awards given by Hindu religious education teachers to Hindu students is in the form of sentences of praise for studying diligently, diligently and with discipline. Apart from that, Hindu students when interacting with teachers at school behave politely, responsibly, and have devotion to the teacher.